“Sistemas de información geográfica (sig) y metodologías de evaluación multicriterio (emc) en la detección de áreas de atención prioritaria en el mejoramiento de acceso a servicios básicos en la ciudad de Quevedo, año 2020” - Haro Palma, Marwin Jordy (2020)
This research was developed in the city of Quevedo; in order to generate a territorial model through a territorial planning and management tool to create scenarios that help distribute equitably and according to those most in need the offer of public and private services in the city. For this, a methodology based on GIS and EMC was applied as support tools for local government to improve the spatial accessibility of the least favoured population in the city of Quevedo in terms of public services. First vector maps were prioritized, maps of all centralities are generated: point (health centers and schools) and linear (public transport routes). The decision criteria were then raised: where vectors are transformed into a raster, in this way, you can work with their pixels as a unit of measure and evaluation for stacking in multicriteria evaluation using the Weighted Linear Combination method. Stripes of similar amplitude (meters) were defined around the centrality, the values are multiplied by a previously set weighted value. It was identified that parishes have access levels, generated a model of accessibility areas in order to verify the quality of life of the population, the organization of the equipment selected for research and geographical space according to unmet needs highlighting the highest profit levels of 53% and high benefit of 35% , however, there are 12% of un benefit-free areas of which it is located in the centrality of parishes May 24 and October 7, where the areas that require greater attention to basic health, education and urban transport services of the city of Quevedo are evident on the map. Keywords: Multicriteria Assessment; Territorial Planning; Population density, Accessibility; Decision criteria.